EFFECTIVENESS OF COMPLETE DENTURES IN RESTORING FUNCTION AND ESTHETICS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Complete edentulism remains a significant global health problem affecting elderly populations and individuals with advanced dental disease. Loss of natural teeth leads to impaired mastication, speech difficulties, facial collapse, and psychological discomfort. Complete removable dentures remain one of the most widely used rehabilitation methods due to affordability and accessibility. The aim of this study is to evaluate the effectiveness of complete dentures in restoring oral function and facial esthetics and to analyze clinical factors influencing treatment outcomes. A comprehensive review and clinical analysis were conducted involving edentulous patients rehabilitated with complete dentures. Functional parameters, esthetic outcomes, and patient satisfaction were assessed through clinical examination and standardized questionnaires. Results demonstrate significant improvement in mastication efficiency, phonetics, facial support, and psychosocial confidence following treatment. However, adaptation time, ridge resorption, and prosthetic design significantly influence long-term success. The study confirms that properly fabricated complete dentures remain an effective therapeutic option when clinical and biomechanical principles are respected. Continuous follow-up and patient education are essential for maintaining functional stability and esthetic satisfaction.